Significant advancement of mass spectrometry imaging for food chemistry. (1st November 2016) - Yoshimura, Yukihiro; Goto-Inoue, Naoko; Moriyama, Tatsuya; Zaima, Nobuhiro
Highlights: MALDI-MSI is a two-dimensional MALDI-MS technology. MALDI-MSI can visualize the spatial distribution of biomolecules in foods. We describe the principles and applications of MALDI-MSI in food related fields. Abstract: Food contains various compounds that have an impact on our daily lives. Many technologies have been established to analyze these molecules of interest in foods. However, the analysis of the spatial distribution of these compounds in foods using conventional technology, such as high-performance liquid chromatography-mass spectrometry or gas chromatography-mass spectrometry is difficult. Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) is considered an ideal complementary approach. MALDI-MSI is a two-dimensional MALDI-MS technology that can detect compounds in a tissue section without extraction, purification, separation, or labeling. MALDI-MSI can be used to visualize the spatial distribution of chemical compounds or biomolecules in foods. Although the methodology of MALDI-MSI in food science is not yet fully established, the versatility of MALDI-MSI is expected to open a new frontier in food science. Herein, we describe the principles and applications of MALDI-MSI in food science and related fields.